Dampak Terapi Intravena pada Balita Berdasar VIP (Visual Infusion Phlebitis) Score - Hernantika Rahmawati (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2014)
Patient safety at hospital is system that nursing care given more safe. When patient  at hospital they may got nosocomial enfection, and some medical procedure have an effect for them, for example intravenous therapy lead to causes of phlebitis. The purpose of this studiy was to  determine the effects of intravenous therapy in infants based on the VIP (Visual Infusion phlebitis) score. Method: The research design was descriptive study. The population in this study are 38infants who received intravenous therapy. Samples are 30 infants by using convenience sampling, research on March 2014 at Nusaindah  room Mardi Waluyo Blitar Hospital. Result : Research found a total of 27 infants no signs of phlebitis, as much as 2 toddlers possibility of early signs phlebitis, and 1 toddler stage beginning phlebitis. Discussion : We expected that nurse will enhance observation of the effects of intravenous therapy.